Transforming Academic Drug Discovery. (18th February 2022) - Meinke, Peter T.
Abstract : A drug accelerator that partners the creative power of academic scientists with drug discovery professionals to consistently advance groundbreaking biological discoveries would be transformational. One such model, the Tri‐Institutional Therapeutics Discovery Institute, evolved a series of best practices for identifying, selecting, executing, and completing academic‐initiated drug discovery projects, is described.